Vol. 2101 : Isotopes: Technologies, Materials and Application (ITMA-2018): V International Conference for Young Scientists, Post-Graduate Students and Students, 19-23 November 2018, Tomsk, Russia; [proceedings]; AIP Conference Proceedings - Martoyan G. A. Gagik Ashot; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Rieznichenko L. Liudmyla (2019, 2019)
Title screen